2014
DOI: 10.3989/scimar.04053.05a
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal photoacclimation patterns in the intertidal macroalga <em>Cystoseira tamariscifolia</em> (Ochrophyta)

Abstract: Summary: Cystoseira tamariscifolia thalli collected from rocky shores and rockpools in winter and summer in Southern Spain were incubated for 7 days in UV transparent cylindrical vessels under outdoor conditions. Photosynthetic activity estimated as in vivo chlorophyll a fluorescence of photosystem II, photosynthetic pigments, antioxidant activity (DPPH assay), phenolic compounds and total internal C and N contents were determined after short-term (3 d) and mid-term (7 d) periods. Maximum quantum yield of PSII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 65 publications
2
32
1
Order By: Relevance
“…In other Cystoseira species, such as C. tamariscifolia, both F v /F m and ETR max also decrease in nutrient enriched treatments in field experiments at various depths (Celis-Plá et al, 2014a). In another experiment, Celis-Plá et al (2014b) found the highest ETR max in C. tamariscifolia in thalli with the lowest internal nitrogen stores i.e., winter compared to summer grown algae. On the other hand, Ek NPQ increased in all cases with the increased CO 2 as an acclimation to high light levels.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In other Cystoseira species, such as C. tamariscifolia, both F v /F m and ETR max also decrease in nutrient enriched treatments in field experiments at various depths (Celis-Plá et al, 2014a). In another experiment, Celis-Plá et al (2014b) found the highest ETR max in C. tamariscifolia in thalli with the lowest internal nitrogen stores i.e., winter compared to summer grown algae. On the other hand, Ek NPQ increased in all cases with the increased CO 2 as an acclimation to high light levels.…”
Section: Discussionmentioning
confidence: 87%
“…Fucoxanthin and violaxanthin levels were not affected in C. compressa whereas in P. pavonica fucoxanthin and violaxanthin increased under 70% PAB conditions, nutrient enrichment and medium CO 2 levels. We used NPQ max as an indicator of photoprotective energy dissipation efficiency (Celis-Plá et al, 2014b), and we also measured phenolic content and antioxidant activity (EC 50 ), both of which can be used as photoprotectors (Celis-Plá et al, 2014a). In C. compressa and P. pavonica NPQ max was higher in all shaded treatments with nutrient enrichment, but not in the fully lit treatments, indicating higher photoprotection when nutrients were elevated and light was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent high irradiance may also lead algae to suffer nutrient stress, as red algae need nitrogen to produce more antioxidant compounds (De la Coba, Aguilera, Figueroa, de Gálvez, & Herrera, 2009). In this regard, nutrient ratios (C:N) have been widely proposed as an indicator for nutrient status in macroalgae (Celis-Plá, Korbee, Gómez-Garreta, & Figueroa, 2014;Figueroa & Korbee, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…the synthesis and accumulation of UV-absorbing compounds such as trihidroxicoumarins in green algae [17], polyphenols in brown algae [15,[18][19][20][21], and mycosporine-like amino acids (MAAs) in red algae species [22][23][24][25][26][27][28].…”
mentioning
confidence: 99%